THE SINUS LIFT PROCEDURE APPLIED IN CASES WHERE THE THICKNESS OF THE ALVEOLAR BONE IS INSUFFICIENT USING DOUBLE PRF AS WELL AS IN THE CASE OF AN INTRASINUS MUCOCELE - Mihaela Mitrea; Laura Iulia Bozomitu; Razvan Tudor Tepordei; Irina Luciana Gurzu; Edlibi Al Hage Walid; Ovidiu Mihail Stefanescu; Simona Alice Partene Vicoleanu; Simona Niculescu; Irina Jemnoschi Hreniuc; Angela Tecuceanu; Allia Dmour; Razvan Radu Maxim; et al. (Romanian Society of Oral Rehabilitation, 2023)
Missing teeth may result in a functional and cosmetic deficit and have traditionally been replaced with dentures or bridges. Dental implants rely on the maintenance of a direct structural and functional connection between living bone and the implant surface, this is termed osseointegration. Osseointegration has undoubtedly been one of the most significant scientific breakthroughs in dentistry over the past 40 years. Insufficient bone volume is a common problem encounter in the rehabilitation of the edentulous posterior maxilla with implant-supported prostheses. The bone available for implant placement may be limited by the presence of the maxillary sinus together with loss of alveolar bone height. Bone volume may be increased by augmentation, commonly the sinus cavity is augmented with autogenous bone or biomaterials or both. Procedures are variously described in the literature as sinus lift, sinus augmentation, sinus floor elevation or augmentation of atrophic maxillary sinus. Implant placement may be combined with sinus augmentation as one-stage technique. Alternatively sinus augmentation may be carried out as some time prior to implant placement as a two-stage technique.